Energy transfer within small molecule/conjugated polymer blends enhances photovoltaic efficiency. Issue 34 (16th August 2017) - Lin, Yu-Che; Su, Yu-Wei; Li, Jia-Xing; Lin, Bo-Hsien; Chen, Chung-Hao; Chen, Hsiu-Cheng; Wu, Kaung-Hsiung; Yang, Yang; Wei, Kung-Hwa
Abstract : We employed ternary blends capable of energy transfer—a synthesized small molecule (SM-4OMe) comprising benzodithiophene (BDT) units (a molecule designed for energy transfer), and a polymer (PTB7-TH) with BDT units with desired packing orientation, and a fullerene—as active layers for single junction photovoltaic devices. Abstract : In this study, we employed ternary blends capable of energy transfer—a synthesized high-band-gap small molecule (SM-4OMe) comprising benzodithiophene (BDT) and rhodanine units (a molecular structure that was designed for energy transfer), a low-band-gap polymer (PTB7-TH) comprising BDT and thienothiophene units with desired packing orientation, and a fullerene—as active layers for single-junction photovoltaic devices. The light absorption of the small molecule and the polymer was partially complementary, owing to their band gap difference, thereby broadening the absorption spectrum of solar light while maintaining the energy band structures that facilitated energy and charge transfer. The synthesized small molecule SM-4OMe and the PTB7-TH had somewhat similar chemical structures—with the same planar BDT donor units—and thus allowed sufficient mixing between them for energy transfer to take place. The power conversion efficiency of a device incorporating a ternary blend of PTB7-TH:SM-4OMe:PC71 BM (0.9 : 0.1 : 1.5, w/w/w) as the active layer, processed with diiodooctane (2 vol%) in chlorobenzene, was 10.4%, which is higher than the value of 8% of the corresponding device incorporating PTB7-TH:PC71 BM (1 : 1.5, w/w)—an increase of 30%. We attribute this enhancement to the energy transfer from the high-band-gap small molecule SM-4OMe to the low-band-gap polymer PTB7-TH and to the optimal phase-separated bulk heterojunction morphology that comprises a mean PC71 BM cluster size of 6 nm, which is lower than 12 nm for the PTB7-TH and PC71 BM binary blends, and slightly better in-plane packing, arising from the inducements of the presence of SM-4OMe. This approach provides a facile and effective way to enhance the power conversion efficiency of single junction organic photovoltaics.